Modelagem computacional de sistemas biológicos - Galvão, Viviane Matos (2009)
In this work, we develope computational models based on multi-agents, regular lattice and complex networks to reproduce biological systems. The sytems simulated are the network of human cell differentiation, chronic chagasic cardiomyopathy after stem cell transplantation, evolution of Chagas’ disease, and enzyme kinetics of invertase. The characterization of the network of human cell differentiation is vital because it can reveal features of the human embryonic development by using the topological and dynamical properties of the differentiation process. A better understanding of Chagas’ disease is necessary because this illness is still incurable and affects millions of people worldwide. The computational modelling of enzyme kinetics of invertase is important because it can describe complex chemical process.